Penerapan Algoritma FP-Growth dalam Penentuan Promosi Kampus - Iskandar Zulkarnain; Hany Maria Valentine (Journal of Computer System and Informatics (JoSYC), 2022)
Campus or college is an institution as well as an institution that is included in the education sector. Now the campus is included in a business sector that is engaged in education. Therefore, the campus is also inseparable from the promotion process. The promotion carried out by the campus has the aim of making prospective new students register on the campus. For private campuses, students are input that can be useful to continue the operational process for the campus. The problem that is still widely found at this time is the process of determining campus promotions is still based on assumptions. Where the assumptions used are not based on a fact or special reference. Determination of promotion on campus can be seen based on the data of students who have registered actively on the campus. From the student data, it can be processed based on Regional Origin, School Origin, Department and Study Program taken. Data mining is a technique used to process large amounts of data. Frequent Pattern Growth Algorithm (FP-Growth) is an algorithm that is included in the data mining association technique. The results obtained in the study that for determining the promotion strategy are if you take the Study Program = Informatics Engineering (PS1) then the Department = Science (J1) and Regional Origin = Deli Serdang (AD1) with a Support value = 30% and a Confidence value = 60% and Department = Science (J1), Regional Origin = Deli Serdang (AD1) with Support = 30% and Confidence = 75%. Based on the results of the process that was carried out, it was found that the promotion target was Deli Serdang, the Department was Science and the Study Program of interest was Informatics Engineering.